1979
DOI: 10.1063/1.438410
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of nitric oxide chemisorbed on Pt(100)

Abstract: The chemisorption of NO on a Pt(100) single crystal surface at 140 and 300 K was investigated by high resolution electron energy loss spectroscopy, combined with Auger electron spectroscopy and LEED. Chemisorption of NO was predominantly molecular. The unreconstructed Pt(100)−1×1 surface was characterized by a single NO stretch frequency at 1615 cm−1 and two low frequency vibrations at 230 and 380 cm−1. These latter modes are likely to represent the Pt–NO stretch and Pt–N–O bending vibrations, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(64 citation statements)
references
References 50 publications
7
57
0
Order By: Relevance
“…The weak band at 403 cm 1 is characteristic of a metal-nitrogen bending mode for an associatively adsorbed species. 17 , 18 This is in agreement with the observation of a bent nitrosyl. The normal dipole selection rule 22 would not allow the observation of such a mode if the adsorbate was bonded perpendicular to the surface.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The weak band at 403 cm 1 is characteristic of a metal-nitrogen bending mode for an associatively adsorbed species. 17 , 18 This is in agreement with the observation of a bent nitrosyl. The normal dipole selection rule 22 would not allow the observation of such a mode if the adsorbate was bonded perpendicular to the surface.…”
Section: Resultssupporting
confidence: 81%
“…The normal dipole selection rule 22 would not allow the observation of such a mode if the adsorbate was bonded perpendicular to the surface. The metal-nitrogen stretching vibration from such a species is expected to be 00-200 " lower in frequency, The results of detailed infrared studies on numerous nttrosyl compounds have been reviewed recently by Pirug, etal, 18 They conclude that the experimental data on both the halogen nitrosyls and transition metal nitrosyls provide evidence for well separated M-N-0 bending and stretching frequencies with the latter always lower than the former.…”
Section: Resultsmentioning
confidence: 99%
“…This system has been studied by many authors, and it has been clear from LEED measurements that a c͑4 ϫ 2͒ structure is formed on the unreconstructed surface. 42,43 Vibrational studies indicated that NO is bound at one type of site. [43][44][45] Recent electronic structure calculations clearly indicate that this must be the bridge type site.…”
Section: A Adsorption On the Fcc(100) Surfacementioning
confidence: 99%
“…42,43 Vibrational studies indicated that NO is bound at one type of site. [43][44][45] Recent electronic structure calculations clearly indicate that this must be the bridge type site. 46,47 Up to now there has been one direct observation of this c͑4 ϫ 2͒ structure, by STM, and this clearly indicated a coverage of 0.25 ML.…”
Section: A Adsorption On the Fcc(100) Surfacementioning
confidence: 99%
“…At high NO coverages, vibrational frequencies of 1710 cm for the (111) face [4,7], 1760 cm' for the (110) face [5] and 1790 cm' for the (100) face [19] have been established by EELS. Assuming an increasing fraction of (111) planes with increasing particle size, these data predict a shift to lower frequencies with larger particles.…”
Section: Infrared Spectramentioning
confidence: 99%